Clinical Features and Factors Associated With Sepsis-Associated Encephalopathy in Children: Retrospective Single-Center Clinical Study - Chen, Yihao; Hu, Yan; Li, Xufeng; Chen, Peiling; Wang, Chun; Wang, Jing; Wu, Jiaxing; Sun, Yueyu; Zheng, Guilang; Lu, Yiyun; Guo, Yuxiong (Frontiers in Neurology, 2022)
Background: Sepsis-associated encephalopathy(SAE) is a common complication in septic patients with a higher ICU and hospital mortality in adults and poorer long-term outcomes. Clinical presentation may range from mild confusion to convulsions and deep coma; however, little is known about SAE in children. We aimed to retrospectively analyze the data for children with sepsis, to illustrate the epidemiology, performance, adverse outcome and evaluate the association between risk factors and SAE in children. Methods: All children with sepsis who were admitted to the Department of Pediatrics, Guangdong Provincial People’s Hospital, Guangzhou, Guangdong, China from January 2010 to December 2020 were retrospectively analyzed. Results: A total of 210 patients with sepsis were retrospectively assigned to the SAE and non-SAE groups, of which 91 (43.33%) were diagnosed with SAE with a mortality of 6.70% (14/210). Significant differences were observed in the level of WBC, PLT, INR, PT, APTT, total protein, Ccr, UREA, BUN, ALT, AST, CK, CK-MB, LDH, PCT, and LAC (P < 0.05). In the risk assessment scales, significant differences were observed in the mGCS, PCIS, PELOD-2, p-SOFA, and PRISM III (P < 0.05). The incidence of septic shock, acute kidney disease, liver dysfunction, and coagulation disorder were higher in the SAE group (P < 0.05). The mechanical ventilation time, CRRT time, ICU stay time(P < 0.001) was longer than that of non-SAE. Both the PCT, Ca2+, septic shock, PELOD-2, and midazolam were identified as independent risk factors, and fentanyl was a protective factor for SAE in pediatric patients (P < 0.05). The main clinical neurological symptoms consisted of agitation, hypnosia, hypnosia alternates agitated, anterior fontanelle full/bulging/high tension, coma, muscle hypertonia, muscle hypotonia, hyperreflexia, focal seizure, and generalized seizure. Conclusions: The incidence of SAE in children was found high and the prognosis poor. In this retrospective study, the identified patients were more susceptible to SAE, with an inflammatory storm with hypocalcemia or septic shock. The use of midazolam will increase the occurrence of SAE, whereas fentanyl will reduce the incidence of SAE, and PELOD-2 may predict the occurrence of SAE.